Gambling (Judi Togel) in Criminology Perspective (Study in Diponegoro and Peterongan Stadium in Semarang City) - Rossa, Novem Ollyvia; Nurmalasari, Rizky; Prameswari, Larasati; Savella, Annisa Diana (Law Research Review Quarterly, 2020)
This research analyzes about lottery gambling as one of social deviations. Togel gambling is seen as one of the forms of social pathology, where social pathology itself is defined as any form of behavior that is deemed inappropriate, violates general norms, customs, formal law or cannot be integrated into general patterns of behavior. Gambling is one of several forms of community disease that in essence is contrary to the Religion, Ethics, and Moral Pancasila, fiber is harmful to the livelihoods and lives of the people, nation and state. Therefore the Government of Indonesia is making efforts to curb gambling, to limit it to the smallest possible environment. With various forms of gambling that are rife in people's daily lives, both overt and covert, some people tend to feel stupid and seem to view gambling as something natural, not breaking the law, so there is no need to question , even some of them argue that gambling is just a small violation. Whereas on the other hand, there is an impression from law enforcement officials who are not so serious in handling this gambling problem.